2016
DOI: 10.1016/j.neubiorev.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Circles of engagement: Childhood pain and parent brain

Abstract: Social interaction can have a profound effect on individual behavior, perhaps most salient in interactions between sick suffering children and their parents. Chronic pain is a difficult condition that can produce considerable changes in behaviors in children that can secondarily have profound effects on their parents. It may create a functionally disabling negative feedback loop. Research supports the notion of alterations in the brain of individuals who observe and empathize with loved ones in acute pain. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 112 publications
1
15
0
Order By: Relevance
“…Empathic reactions of negative situations (like caring for a relative with pain or, in this case, dementia) can lead to stress or negative changes in neural networks. 29 To ensure the safety and well-being of the participants, immediately after the training, an individual conversation with the trainer is organised. During this conversation, the participants discuss their experiences in the simulator, and the trainer comforts the participants if needed.…”
Section: Methods and Analysesmentioning
confidence: 99%
“…Empathic reactions of negative situations (like caring for a relative with pain or, in this case, dementia) can lead to stress or negative changes in neural networks. 29 To ensure the safety and well-being of the participants, immediately after the training, an individual conversation with the trainer is organised. During this conversation, the participants discuss their experiences in the simulator, and the trainer comforts the participants if needed.…”
Section: Methods and Analysesmentioning
confidence: 99%
“…Because of this connection, children with life-limiting illness may be directly affected by the psychological well-being of their parents. For example, a parent’s response to their child’s pain may affect the child’s experience of that pain [ 38 ]. In one study, children whose parents were oriented toward their pain and distress, without being self-oriented (responding out of self-protection to the distress that the child’s pain may have caused in the parent) had less observable pain and distress and a more positive disposition during cancer treatments [ 39 ].…”
Section: Care For the Parent Directly Impacts The Childmentioning
confidence: 99%
“…Indeed, findings amongst healthy schoolchildren [7] and children with chronic pain [8] have demonstrated that parental distress when anticipating/observing their child's pain contributes to increased restriction of child pain and painful physical activity. While controlling pain has adaptive value by protecting from further harm, persistent efforts to control child's pain may contribute to increased child disability by diminishing engagement in daily activities [12,38,39,53,54,55,71]. Given the central role of parental emotional distress, parental emotion regulation ability is considered fundamental in buffering (or strengthening) the occurrence of distress and pain control behaviours elicited by child's pain displays [25,68,69].…”
Section: Introductionmentioning
confidence: 99%